2000
DOI: 10.1038/35013070
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation attenuates the systemic inflammatory response to endotoxin

Abstract: Vertebrates achieve internal homeostasis during infection or injury by balancing the activities of proinflammatory and anti-inflammatory pathways. Endotoxin (lipopolysaccharide), produced by all gram-negative bacteria, activates macrophages to release cytokines that are potentially lethal. The central nervous system regulates systemic inflammatory responses to endotoxin through humoral mechanisms. Activation of afferent vagus nerve fibres by endotoxin or cytokines stimulates hypothalamic-pituitary-adrenal anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

106
2,877
10
83

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 3,599 publications
(3,166 citation statements)
references
References 26 publications
106
2,877
10
83
Order By: Relevance
“…In contrast, our study suggested that unilateral vagotomy not only aggravated the abnormality of ICM rats and increased the inducibility quotient of ventricular arrhythmias but also attenuated the effects of eliciting CAP. It was also reported that vagotomy attenuated the anti‐inflammatory effect of CAP and thereby enhanced cytokine release in response to LPS treatment 41, 42. Thus, vagotomy, performed in an ICM rat, increased the release of cytokines and collagens and altered the sympathetic/parasympathetic ratio, which served as a harmful role of ventricular arrhythmia.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, our study suggested that unilateral vagotomy not only aggravated the abnormality of ICM rats and increased the inducibility quotient of ventricular arrhythmias but also attenuated the effects of eliciting CAP. It was also reported that vagotomy attenuated the anti‐inflammatory effect of CAP and thereby enhanced cytokine release in response to LPS treatment 41, 42. Thus, vagotomy, performed in an ICM rat, increased the release of cytokines and collagens and altered the sympathetic/parasympathetic ratio, which served as a harmful role of ventricular arrhythmia.…”
Section: Discussionmentioning
confidence: 93%
“…Conventional risk factors (abnormal body mass index (BMI), abnormal lipogram, smoking, hypertension, diabetes mellitus, family history of cardiac disease and a personal history of cardiac disease) [8,9], accelerated atherosclerosis due to inflammation [7,10,11], and autonomic dysfunction [12][13][14][15] can all play a role in the etiopathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been demonstrated that the cholinergic nervous system can regulate inflammation via its principal neurotransmitter, ACh, a concept referred to as the "cholinergic antiinflammatory pathway" (5). ACh can interact with members of the nAChR family.…”
mentioning
confidence: 99%
“…The ␣7nAChR is expressed by various immune cells, including monocytes (15), macrophages (5,16), T and B lymphocytes (17,18), and dendritic cells (19). In addition to this classic ␣7nAChR, the human genome contains an alternative ␣7 transcript designated dup␣7 or "cholinergic receptor family with sequence similarity to 7A" (CHRFAM7A) (20).…”
mentioning
confidence: 99%